Designing augmented reality problem-based learning in plant growth: Addressing the development of 21st-century skills - Nurul Asikin; Arinda Eka Lidiastuti; Novie Ary Priyanti; M. Arsyad; Achmad Shobirin; Annisa Qadri Tanjung (University of Muhammadiyah Malang, 2026)
Background: The concept of plant growth is fundamental to biology education. However, conventional instruction often emphasizes conceptual memorization rather than active inquiry, collaboration, and problem-solving, limiting opportunities for students to develop essential 21st-century skills. Objectives: This study aims to analyze students' 21st-century skills profiles as a needs assessment to inform the design of an Augmented Reality Problem-Based Learning (ARPBL) model for plant growth learning. Methods: A descriptive quantitative approach was employed involving 274 secondary school students from 33 schools in Indonesia. Data were collected using a validated Likert-scale questionnaire measuring four core competencies: critical thinking, creativity, collaboration, and communication. The results were used to inform the development of an ARPBL prototype integrating mobile-based augmented reality with problem-based learning scenarios. Results: The findings indicate that students demonstrate moderate to high levels of creativity and communication, while critical thinking remains at a basic level. This imbalance underscores the need for more interactive and technology-enhanced instructional strategies. The ARPBL model incorporates 3D visualization and contextual problem-solving activities, offering an immersive learning experience that enhances both conceptual understanding and skill development. Conclusion: ARPBL shows strong potential to address cognitive and skill gaps in biology education and is recommended to promote deeper understanding and strengthen students' 21st-century competencies.